Fast Intra Prediction Mode Decision Algorithm for HEVC - Mengmeng Zhang; Jianfeng Qu; Huihui Bai (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper proposes a novel fast intra-prediction algorithm that exploits the Sobel operator to replace the Hadamard transform used in the Rough Mode Decision (RMD) process of intra prediction in High Efficiency Video Coding (HEVC). First, the Sobel operator is used to calculate the vector direction of each pixel. A judgment is then made on which prediction mode the vector belongs to, and a histogram is applied in the scheme to generate the statistics of prediction modes for each prediction unit. Finally, the prediction mode candidates are placed in the candidate list for the rate-distortion optimization process. Experimental results show that our proposed algorithm for RMD significantly reduces the complexity of the encoder with an acceptable degradation of quality and BD-rate compared with HM7.0. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3396